The Influence of Capital Intensity, Inventory Intensity and Institutional Ownership on Tax Avoidance With Company Size as Moderation - Sugito, Sugito; Tarmidi, Deden (Universitas Pamulang, 2025)
This research aims to examine the influence of capital intensity, inventory intensity, and institutional ownership on tax avoidance with company size as a moderating variable. This research used a sample of 13 manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2023. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with the help of the STATA 17 application. The results of the study showed that intensity capital has a negative effect on tax avoidance, while institutional ownership has no effect on tax avoidance. However, inventory intensity does not show a significant influence on tax avoidance. Company size is able to moderate the influence of capital intensity on tax avoidance, but weakens the influence of inventory intensity and institutional ownership on tax avoidance. These findings provide important implications for companies in understanding the factors that influence tax avoidance strategies. Apart from that, this research can be a reference for the Directorate General of Taxes to increase the effectiveness of tax policies in the manufacturing sector.